Itm2a silencing rescues lamin A mediated inhibition of 3T3-L1 adipocyte differentiation. (2nd October 2017) - Davies, Stephanie J.; Ryan, James; O'Connor, Patrick B. F.; Kenny, Elaine; Morris, Derek; Baranov, Pavel V.; O'Connor, Rosemary; McCarthy, Tommie V.
ABSTRACT: Dysregulation of adipose tissue metabolism is associated with multiple metabolic disorders. One such disease, known as Dunnigan-type familial partial lipodystrophy (FPLD2) is characterized by defective fat metabolism and storage. FPLD2 is caused by a specific subset of mutations in the LMNA gene. The mechanisms by which LMNA mutations lead to the adipose specific FPLD2 phenotype have yet to be determined in detail. We used RNA-Seq analysis to assess the effects of wild-type (WT) and mutant (R482W) lamin A on the expression profile of differentiating 3T3-L1 mouse preadipocytes and identified Itm2a as a gene that was upregulated at 36 h post differentiation induction in these cells. In this study we identify Itm2a as a novel modulator of adipogenesis and show that endogenous Itm2a expression is transiently downregulated during induction of 3T3-L1 differentiation. Itm2a overexpression was seen to moderately inhibit differentiation of 3T3-L1 preadipocytes while shRNA mediated knockdown of Itm2a significantly enhanced 3T3-L1 differentiation. Investigation of PPARγ levels indicate that this enhanced adipogenesis is mediated through the stabilization of the PPARγ protein at specific time points during differentiation. Finally, we demonstrate that Itm2a knockdown is sufficient to rescue the inhibitory effects of lamin A WT and R482W mutant overexpression on 3T3-L1 differentiation. This suggests that targeting of Itm2a or its related pathways, including autophagy, may have potential as a therapy for FPLD2.